CHANGES IN THE QUALITY OF LIFE AND SEXUAL FUNCTION IN WOMEN WITH PELVIC PROLAPSE AFTER LIGATION OF COLPOPEXY WITH POLYPROPYLENE MESH - A. D. Kaprin; A. A. Kostin; V. B. Filimonov; R. V. Vasin; I. V. Vasina (Исследования и практика в медицине)
Objective. To evaluate the effect of vaginal operations to eliminate pelvic prolapse using polypropylene implants on quality of life and sexual function of patients.Materials and methods. The study included 93 women with genital prolapse II - IV stage, underwent extraperitoneal colpopexy polypropylene implant. The patients were divided into two groups according to the method of vaginal ligation of colpopexy: in group 1 (n = 50) included patients who underwent the surgery perforated polypropylene implant "Cineplex" (LINTEX, Russia) according to the developed method (patent RF № 2538796); 2 (n = 43) group included patients who had an operation using standard kits with polypropylene mesh (ProliftTM, Prolift™ + M, ProsimaTM ETHICON Women's Health & Urology" Johnson & Johnson Company, USA). The quality of social and sexual life was assessed using the questionnaire to calculate the index of sexual function in women (Female Sexual Function Index (FSFI)) and non-specific questionnaire of quality of life SF-36 preoperatively and 6 months after.Results. In patients prior to surgical intervention compared with the general population indicators of quality of life statistically significantly reduced for all scales. Physical health component (PHC) reduced by 57.8% in the 1st group and 59.5 per cent in the 2nd group, and psychological health (PsCH) by 42% and 43.5% respectively groups compared with the general population indicators. In the postoperative period, significant improvement in the quality of life in the 2 treatment groups compared with preoperative observed in all parameters. In group 1 noted that PHC restored by 32%, and PsCH 40.7%; in the 2nd group - PHC improved by 26.1% and PsCH of 29.4% (Fig. 2). Comparative analysis of the quality of life of patients after surgery compared groups showed that in group 1 was able to significantly (p<0.05) improve social functioning and mental health patients in comparison with group 2. The total score of the index of sexual function after surgery was significantly increased in the 1st group from 15.8 ± 5.3 to 25.2 ± 4,2; in the 2nd group - from 15.5 ± 5 to 21.4 ± 6. Intergroup statistical analysis of the index of female sexual function after surgical treatment of pelvic prolapse showed significant improvement (p<0.05) in the 1st group for all indicators (desire, arousal, lubrication, orgasm, satisfaction and total score), in addition to the indicator dyspareunia, in comparison with patients of the 2nd group.Conclusions. The pelvic organ prolapse in women significantly affects their quality of life and becomes the cause of sexual disorders. Vaginal reconstruction of pelvic prolapse using polypropylene implants in sexually active women leads to better sexual function by eliminating the loss of the walls of the vagina and urinary incontinence. However, the peculiarities of surgical intervention are responsible for the reduced orgasmic function and appearance of dyspareunia. In patients after vaginal ligation of colpopexy using perforated polypropylene implant according to the developed method was significantly improved sexual function in all indicators of the FSFI questionnaire in comparison with the patients operated using a standard set with polypropylene implant for the correction of pelvic prolapse.